Practical Issues in Implementing TRNGs in FPGAs Based on the Ring Oscillator Sampling Method - Cret, O.; Suciu, A.; Gyorfi, T. (Symbolic and Numeric Algorithms for Scientific Computing, Proceedings, 2008)
Field programmable gate arrays (FPGAs) are an increasingly popular choice of platform for the implementation of cryptographic systems. For all such systems, random numbers are essential. One of the most well-known methods for producing true random number sequences in FPGAs is based on the phenomenon of jitter and built upon ring oscillators. This paper describes how to overcome the placement sensitivity caused by the different physical properties of the logic elements, thus extending the portability of TRNGs on various FPGA boards. Our design offers an easy implementation, but in the same time maintains the good quality and high generation throughput of random numbers.